Fourteen new species of the genus Thubdora Park, 2018 (Lepidoptera: Gelechioidea: Lecithoceridae) from Uganda, and three new combinations in Ptilothyris Walsingham, 1897 from DR Congo - Park, Kyu-Tek; Mey, Wolfram; Koo, Jun-Mo; de Prins, Jurate; Akite, Perpetra; Cho, Soowon (Zootaxa, 2020)
Fourteen new species of the Afrotropical genus Thubdora Park, 2018 (Lecithoceridae: Torodorinae) are described from Uganda: Thubdora afropyralidis Park, sp. nov., T. fruticosa Park, sp. nov., T. kibalensis Park, sp. nov., T. klenodes Park, sp. nov., T. latidiscalis Park, sp. nov., T. mirinae Park, sp. nov., T. nemorosa Park, sp. nov., T. retusivalva Park, sp. nov., T. umbratilis Park, sp. nov., and T. wooriana Park, sp. nov. in the aciphalla species-group (10 species); and T. corystos Park, sp. nov., T. narusia Park, sp. nov., T. trigonoides Park, sp. nov., and T. villosiphalla Park, sp. nov. in the acutalis species-group (four species). Four species are reported for the first time from Uganda: T. ambliodes Park, 2018, T. bilobella Park, 2018, T. ealaensis Park & De Prins, 2019, and T. ghesquierei Park & De Prins, 2019; and the females of T. ealaensis and T. ghesquierei are newly described, and their genitalia are illustrated. In addition, three species of Ptilothyris Walsingham, 1897 previously recorded from DR Congo are transferred to Thubdora: T. brachysema (Meyrick, 1938), comb. nov., T. crocophracta (Meyrick, 1938), comb. nov., and T. nemophorella (Ghesquière, 1940), comb. nov. Lectotypes for T. brachysema and T. crocophracta are designated herein. Identifications of the new species and corresponding females were confirmed based on the comparison of COI barcode sequences. Adults and genitalia of all the new species and the three species transferred from Ptilothyris are illustrated.